Konseling Individual untuk Meningkatkan Self-Efficacy Belief pada Ibu Hamil Primigravida Trimester Kedua di Klinik “X” Bandung - I Gusti Ayu Putri Devy Rosiana; O. Irene Prameswari Edwina; Lie Fun Fun (Humanitas (Jurnal Psikologi), 2018)
This reserarch is part of the thesis conducted by I Gusti Ayu Putri Devy Rosiana. This study was conducted to obtain an overview of the effect of individual counseling to improve self-efficacy belief in second trimester primigravid pregnant women at “X” clinic in Bandung city in order to decrease anxiety related to delivery. According to Beck et al (1985, 2005) high anxiety is due to low assessment of individual coping ability in overcoming a threatening situation. According to Bandura (2002) the degree of self-efficacy belief can be enhanced through its sources. Therefore, to improve self-efficacy belief will be done through the acquisition of new understanding of self-efficacy sources. The sample involves 2 primigravid pregnant women in second trimester. The results is individual counseling can improve the degree of self-efficacy belief and decrease anxiety related to delivery. Practical advice is, counselors can provide individual counseling to improve self-efficacy belief in facing delivery for primigravid pregnant women.